2008
DOI: 10.1139/a08-003
|View full text |Cite
|
Sign up to set email alerts
|

Forest management and soil respiration: Implications for carbon sequestration

Abstract: It is recognized that human activities, such as fossil fuel burning, land-use change, and forest harvesting at a large scale, have resulted in the increase of greenhouse gases in the atmosphere since the onset of the industrial revolution. The increasing amounts of greenhouse gases, particularly CO2 in the atmosphere, is believed to have induced climate change and global warming. With the ability to remove CO2 from the atmosphere through photosynthesis, forests play a critical role in the carbon cycle and carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 279 publications
(293 reference statements)
3
54
0
4
Order By: Relevance
“…We had expected that soil respiration in both reference forested wetlands would be lower than in the Ag site, as is typically the case for reducing environments (Schlesinger 1997, Peng et al 2008), but we found no differences. A drought during the first year of the study period likely suppressed soil respiration in the drier Ag soils and increased soil respiration in the reference forested wetlands, but patterns were not markedly different in the second year, when precipitation patterns were closer to normal (Fig.…”
Section: áYrmentioning
confidence: 38%
See 1 more Smart Citation
“…We had expected that soil respiration in both reference forested wetlands would be lower than in the Ag site, as is typically the case for reducing environments (Schlesinger 1997, Peng et al 2008), but we found no differences. A drought during the first year of the study period likely suppressed soil respiration in the drier Ag soils and increased soil respiration in the reference forested wetlands, but patterns were not markedly different in the second year, when precipitation patterns were closer to normal (Fig.…”
Section: áYrmentioning
confidence: 38%
“…Since this restored wetland is a young, aggrading forest, compared to the conventionally managed Ag site and the two mature forested wetlands (FW-dry and FW-wet), the restored wetland undoubtedly represents a stronger CO 2 sink in soils and plant biomass (Odum 1969, Pregitzer and Euskirchen 2004, Peng et al 2008. Furthermore, if we only consider N 2 O and CH 4 fluxes, the drier areas of the restored wetland produced significantly less trace gas CO 2 equivalents than either the agricultural field or the forested wetlands (Fig.…”
Section: áYrmentioning
confidence: 99%
“…Therefore, studies examining patterns and mechanisms of soil CO2 in response to management practices are essential. Such studies are critical to accurately predict effects of forest management on the C cycle and to develop appropriate forest management strategies aimed at reducing atmospheric CO2 concentrations (Peng et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…산림을 통한 토양 CO 2 방출에 관여하는 일련의 과정 들은 인간의 활동이나 자연 재해로부터 영향을 받으며 (Jandl et al, 2007;Peng et al, 2008), 이러한 반응에 가 장 크게 기여하는 요인은 토양 온도, 토양 수분 및 양분 유 효도 같은 입지환경요인과 토양 내 유기탄소 같은 기질 (substrate quality)의 차가 원인으로 알려져 있다 (Dong et al, 1998;Deng et al, 2010). 한편, 산림토양에서 발생 하는 CO 2 방출은 시⋅공간적으로 상당한 변이가 발생 하며 (Konda et al, 2010), 토양 수분 및 양분 유효도 같은 산림환경 요인과 산림생태계가 위치한 지리적 위치 및 계절 변화에 민감하게 반응하였다 (Konda et al, 2010).…”
Section: 서 론unclassified